"It's Fine; I'm Fine": Considerations for Trauma-Informed Healthcare Practices. Issue 4 (20th April 2020) - McDonald, Jessica
ABSTRACT: There is a myriad of factors that impact the degree to which a person engages in effective health behaviors, particularly in help-seeking and service utilization. Trauma exposure is among one of the more complex factors which impacts these behaviors due to the idiosyncratic nature of the individual's understanding of, and reactions to, the trauma. Moreover, the type of trauma experience arguably impacts the ways in which an individual interacts with health-care systems. This document explores variables to consider in trauma-informed case conceptualization in hospital settings in an effort to increase effective health behaviors for those who have experienced trauma of any kind.